Oxxxymiron and Pushkin: An Intertextual Analysis of the Rap Album Gorgorod - Дементьев, Илья (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]This article aims to analyze the intertextual references found between Gorgorod (2015), the rap album by the contemporary Russian rapper Miron Fyodorov (Oxxxymiron), and the tragedy Boris Godunov, written by Alexander Pushkin (1825). The author of this article reveals and emphasizes the language and semantic similarities between the two texts, including the parallels in images of the main characters Grigoriy Otrepyev (future False Dmitri I) and a poet Marc/Mark. This article emphasizes the anagrammatism among the techniques that Oxxxymiron applies. In particular, the author implicitly introduces the name of Grigoriy Otrepyev in the text: Na pRIGOvOREnnykh TRyaPyE, narod vo vsyu GlOtku ORET (“The condemned are dressed in rags; people are yelling”). Another important device is a reference to the Babylonian pretext (to the biblical myth about the construction of the Tower of Babel). The image of the tower is common to Boris Godunov (the tower in the dream of Grigoriy) and Gorgorod (the chapter “Tower of Ivory” and an illustration of the Tower of Babel by Pieter Bruegel the Elder). The analysis demonstrates that the concepts of power and creativity in the texts written by Oxxxymiron are in many respects consonant with the reflections of Alexander Pushkin and are inscribed in the European cultural tradition.Oksimoronas ir Puškinas: intertekstuali albumo „Gorgorod“ analizėStraipsnyje interpretuojami šiuolaikinio Rusijos reperio Mirono Fiodorovo repo albumo „Gorgorod“ (2015) ir Aleksandro Puškino tragedijos „Borisas Godunovas“ (1825) intertekstualūs ryšiai. Konstatuojamos kalbinės ir prasminės šių dviejų kūrinių sąšaukos. Išanalizuotas abiejų kūrinių herojų – Grigorijaus Otrepjevo (būsimo apsišaukėlio Dmitrijaus) ir poeto Marko charakteristikų paralelizmas. Pateikta hipotezė apie albumo „Gorgorod“ „bailoniškąją potekstę“ (biblinis mitas apie Babelio bokšto statybą). Dramblio kaulo bokšto įvaizdis Fiodorovo (Oksimorono) albume „Gorgorod“ gretinamas su Grigorijaus Otrepjevo susapnuotu bokštu ir su Piterio Breigelio Vyresniojo paveikslo „Babelio bokštas“ reprodukcija, kuri puošia albumo „Gorgorod“ viršelį. Jei hipotezė apie dviejų analizuojamų kūrinių „babiloniškąją potekstę“ yra teisinga, M. Fiodorovo valdžios ir kūrybos koncepcija gali būti įtraukta į Europos kultūros tradiciją.
Keywords: Pushkin, “Boris Godunov”, Oxxxymiron, Miron Fyodorov, “Gorgorod”, intertextuality